The Effect of Production and Macroeconomic Variables on Indonesia's Shrimp Exports - Agus Tri Basuki; Lusiana Nur Pratiwi (SEAN Institute, 2024)
The aim of this research is to analyze the influence of changes in world shrimp prices, changes in the dollar exchange rate against the rupiah, changes in International Gross Domestic Product, and changes in inflation on changes in shrimp exports. The model in this research uses Error Correction Model (ECM) regression. The ECM model is the most suitable model to use in analyzing export behavior in Indonesia. This research uses time series data from 1990 to 2022. The results of this research show that changes in world shrimp production and changes in inflation have a positive and significant effect on changes in Indonesian shrimp exports in the short term. Meanwhile, changes in world shrimp prices have no effect on changes in shrimp exports, changes in international GDP have a negative effect and changes in exchange rates have no effect on changes in Indonesian shrimp exports. In the long term, it shows that changes in world shrimp production, changes in world shrimp prices, changes in Indonesian inflation have a positive influence on changes in Indonesian shrimp exports, while changes in international GDP have a negative influence on changes in Indonesian shrimp exports. Because changes in inflation and changes in shrimp prices have a negative impact on changes in shrimp exports, the government should pay attention to simple shrimp cultivation techniques that benefit shrimp farmers, thereby increasing the competitiveness of shrimp exports in the international market.